ANALISA PENGARUH CURRENT RATIO, STRUKTUR MODAL, DAN BIAYA OPERASIONAL TERHADAP PAJAK PENGHASILAN BADAN TERUTANG - Amelia, Yessica; Purwanti, Ika (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This research aims to determine the influence of research variables on the the Corporate Income Tax (PPH) owed, including : (1) the current ratio variabel; (2) debt to equity ratio variabel; (3) long-term debt to asset ratio variabel; (4) variable operational costs; and (5) the simultaneous influence of the variables current ratio, debt to equity ratio, long-term debt to asset ratio, and operational costs on the Company's PPH payable. This research is quantitative research using secondary data from annual financial reports. Samples were taken using a purposive sampling technique with a total sample of 18 companies from 48 food and beverage companies listed on the Indonesia Stock Exchange in 2018-2022 so that the research data analyzed amounted to 90. The data analysis techniques used were descriptive statistics, classical assumption tests, and tests. hypothesis. The research results show simultaneously: current ratio, debt to equity ratio, long-term debt to asset ratio, and operational costs have a significant effect on corporate income tax payable.